Metastasis Related Epithelial-Mesenchymal Transition Signature Predicts Prognosis and Response to Immunotherapy in Gastric Cancer - Song, Junquan; Wei, Rongyuan; Huo, Shiying; Gao, Jianpeng; Liu, Xiaowen (Frontiers in Immunology, 2022)
Background: Increasing evidence has revealed the effect of epithelial-mesenchymal transition (EMT) on tumor microenvironment and cancer treatment. However, EMT-based signature to predict prognosis and therapeutic effect in gastric cancer (GC) has not been established. Methods: Firstly, the differentially expressed genes (DEGs) between paired primary and ovarian metastatic tumors were identified through RNA-seq, and we constructed metastasis related EMT signature (MEMTS) based on DEGs and EMT gene set. Then, both The Cancer Genome Atlas (TCGA) cohort and Asian Cancer Research Group (ACRG) cohort were analyzed to explore the relationship between MEMTS and prognosis in GC. Samsung Medical Center (SMC) cohort and two individual immunotherapy treatment cohorts were utilized to evaluate the predictive value of MEMTS on the response to adjuvant therapy and immunotherapy, respectively. Finally, the relationship between MEMTS with tumor environment and immune escape mechanisms was investigated. Results: High MEMTS predicted the poor overall survival and progressive free survival in patients with GC. Patients with low MEMTS gained more benefits from adjuvant chemoradiotherapy than those with high MEMTS. MEMTS reliably predicted the response to immunotherapy in GC (area under the curve = 0.896). MEMTS was significantly associated with cancer associated fibroblasts and stromal score in the tumor microenvironment. Conclusion: MEMTS serves as a potential biomarker to predict the prognosis and response to adjuvant therapy and immunotherapy in GC. MEMTS-based evaluation of individual tumors enables the personalized treatment for GC patients in the future.